School and Education as a Part of Public Administration in the Perspective of a Smart Organisation – Selected Attributes - Raszewska-Skałecka, Renata (University of Wroclaw. Faculty of Law, Administration & Economics, 2019)
The study is aimed at emphasising the selected aspects of smart education with regard to the school perceived as an intelligent knowledge-based organisation challenged by state-of-the-art civilisational and technological educational solutions. The study focuses on school and education with respect to the structure and function of public administration perceived as an intelligent organisation. School and educational services will determine and influence future generations of public administration staff. Their brainpower as well intellectual resources (knowledge, skills and experience) will serve the welfare of the society. Highly intelligent administration may win the respect for the organisation itself and for its services rendered to the society.
Keywords: inteligentna administracja; inteligentna edukacja; usługi edukacyjne; szkoła ucząca się; społeczeństwo informacyjne